DEVELOPING SPEAKING MATERIALS BASED ON THE COMMON EUROPEAN FRAMEWORK OF REFERENCE (CEFR) FOR INCREASING THE STUDENTS’ SPEAKING SKILL - Yuniarti, Yuniarti (Jurnal Pedagogy, 2016)
This study was aimed to describe the steps of developing speaking materials based on the Common European Framework of Reference (CEFR) for increasing the students’ speaking skill of the A2 students of IDeA Indonesia, Metro, Lampung. This research included in research and development (R&D). The mixed-method was used in this research. The combinations of qualitative and quantitative techniques were used for analysing the data. The qualitative data were collected by conducting interviews, field notes, the teacher’s feedback, observations and experts’ comments. Interviews were conducted for gaining the students’ needs analysis and evaluation of the materials. The quantitative data were collected by conducting questionnaires for needs analysis, trying out the materials and evaluating the materials. The data were analysed by using descriptive analysis with percentage. Based on the needs analysis, it was found out that the students need specific materials for speaking. In designing syllabus, the old syllabus must be improved and added with some practical speaking materials. There were eleven units in the handout. Each unit consisted of speaking materials, writing activities, spoken activities, notes and let’s make summary. The students said that the developed materials was challenging and interesting. Two experts said that the materials were very good. The results of the materials implementation showed the improvements of the speaking score. The improvement of students’ speaking score after implementing the handout was 38 scores for 15 students and the average of the score improvement was 2.53. The highest improvement score was 2 or 33.33%. This improvement indicated that the product or the designed materials for A2 students based on CEFR was effective to improve the students’ speaking skill.